Real‐world clinical diagnostics of heart failure patients with reduced or preserved ejection fraction. (18th March 2020) - Huusko, Jenni; Purmonen, Timo; Toppila, Iiro; Lassenius, Mariann; Ukkonen, Heikki
Abstract: Aims: The study aimed at investigating the use of guideline‐recommended diagnostic tools and medication in patients with heart failure (HF) in specialty care in Southwest Finland. We also compared the characteristics of the diagnosed and undiagnosed patients as well as laboratory tests, procedures, and treatments in everyday clinical practice. Methods and results: Patients diagnosed with HF, cardiomyopathy, or hypertension‐induced heart disease ( n = 20 878, primary cohort) or not diagnosed with HF but having a record of elevated N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) (>125 ng/L, n = 24 321, secondary cohort) were included in the study from the specialty care patient register of the Hospital District of Southwest Finland during the years 2005–2017. Among patients with an International Classification of Diseases, Tenth Revision (ICD‐10) code for HF, only 50% had ejection fraction (EF) data to be found by data mining from the electronic health records. Of these patients, 39% ( n = 4042) had EF ≤ 40% [HF with reduced EF (HFrEF)] and 61% ( n = 6347) had EF > 40%. Elevated NT‐proBNP together with EF > 40% narrowed down the number to 4590 patients, a population defined as HF with preserved EF (HFpEF) patients. HFpEF patients were further stratified into HF with mildly reduced EF (HFmrEF; EF 41–50%, n = 1468) and EF > 50% patients ( n = 3122) to compare clinical characteristics. NT‐proBNP was higher within the HFrEF patients vs. HFpEF 4580 [inter‐quartile range (IQR): 2065–9765] vs. 2900 [2065–9765] ng/L, P < 0.001. Baseline co‐morbidities differed between HFpEF and HFrEF groups. Further, HFpEF patients had more procedures and lab tests taken prior to diagnosis than had HFrEF patients. HFmrEF patients were found to resemble more HFrEF than EF > 50% patients. In 70% ( n = 17 156) of patients in the secondary cohort, the NT‐proBNP concentrations were >300 ng/L, median was 1090 (IQR 551–2558) ng/L and EF 58.4 ± 12.1% ( n with EF available = 6845). Reduced EF was present in 6.8% of patients lacking HF diagnosis. Conclusions: Half of the patients with ICD‐10 code for HF did not have EF data available after a visit at specialty care. In particular, the diagnosis of HFpEF seems challenging, reflected as an increase in procedures and laboratory test preceding diagnosis compared with those in HFrEF patients. Also, a large proportion of patients did not have HF diagnosis, yet they presented elevated NT‐proBNP concentrations and clinical characteristics resembling those of HFpEF patients.